The Significance of the Role of Village Government as the Frontline of Stunting Management Towards the Golden Indonesia 2045 - Maharani, Defi; Cahyani, Sintia Dwi; Siswoyo, Mukarto (Indonesian Journal of Advanced Research, 2025)
Stunting is one of the challenges in public health that requires effective intervention from the village government. The purpose of this study is to determine the role of the Kramatsampang Village government in preventing and handling stunting and the obstacles faced in its implementation. The theoretical framework used is Mintzberg's role theory, which consists of three role categories: (1) Interpersonal Role, (2) Informational Role, and (3) Decision-Making Role. The descriptive qualitative method was applied in this study with data collection techniques in the form of interviews, observations, and documentation studies. Data analysis was conducted through three stages, namely Data Reduction (Simplification), Data Presentation, and Conclusion Drawing. The results showed that the Kramatsampang Village Government has played an optimal role in supervising health and nutrition programs, although there are obstacles such as cultural influences and low public awareness of environmental hygiene and the importance of balanced nutrition. Overall, the Kramatsampang Village Government has shown a significant role in dealing with stunting, but more effective strategies are still needed in improving information affordability, community participation, and optimizing resources to support the sustainability of the stunting prevention program.